Neurotic Solution Of Voitski Against His Family In Uncle Vanya Drama By Anton Chekov: An Interpersonal Psychoanalytic Approach - Oktariani, Devi Putri; , Drs. Abdillah Nugroho, M.Hum; , Drs. Sigit Haryanto, M.Hum (2013)
In this research the researcher discusses neurotic solution of Voitski as major character in Uncle Vanya dram. Objective of the study is to analyze neurotic solution related with Karen Horney theory an interpersonal pshychoanalytic approach. The type of the research is qualitative research. There are two types of the data, namely Primary and secondary data. Primary data source come from Uncle Vanya drama and secondary data come from book, website, or any information related to the study. Then, the data are analyzed based on structural element and an interpersonal pshychoanalytic approach by Karen Horney theory. In analyzing the data, this research applies descriptive analysis. The results of the study show; firstly, it is about structural analysis of Uncle Vanyadrama script. The character of Uncle Vanya drama script consists of 3 main characters such as Ivan (Vanya) Voitski, Alexander Serebrakoff, a retired professor and Helena. While the minor characters consist of Michael Astroff, Sonia and Marina The setting of place on Uncle Vanya drama script is in a house of Vanya's family in Russia. From the whole dialogue it can be seen that Chekov wants to tell the situation of the real life of Russia in 1897. The plot of the story consists of beginning, complication, climax and resolution. The point of view of Uncle Vanya drama script coming fromthe director Anton Chekov. The theme of this novel is "The wealth is the root of destruction on the family". Secondly, Moving toward people of Vanya is the way of Vanya to get the solution from people. This is one of neurotic solution that shows that people not live alone and they will need other people. Moving against people of Vanya appears when he knows that the professor has one purpose on his house. Vanya tries to strive against his mother opinion related with the professor. Vanya wants to show that he can protect his family. Moving away from people of Vanya appears where in a certain situation Vanyacan not handle the problem and he thinks that stay alone is the wise decision for him